Pemaknaan Tagline ‘Make It Real’ dalam Iklan Handphone Realme Versi ‘Kebaikan Ramadhan’ - Wahyu Wary Pintoko (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2025)
This study aims to analyze the interpretation of the tagline “Make It Real” in the Realme Ramadan advertisement through Charles Sanders Peirce's semiotic approach. Realme, as a leading smartphone brand, has successfully increased its market share through effective marketing strategies, including the use of advertisements that are relevant to the culture and values of society. The